Narrating the temporalities, localities, and socialities of future English teachers’ professional identities - Sarasa, María Cristina; Solís, Daniela (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
This research article explores the storied construction of future teachers’ professional identity as expressed in field texts including multiple narratives and journal entries co-composed with ten students at an EL teacher education program in an Argentinean state university. Its rationale is grounded in a narrative view of identity. Its methodology is that of narrative inquiry, which studies experience as a narrated phenomenon. By narratively analyzing the collected field texts, our inquiry thematizes the process of becoming an English teacher within this initial teacher education program in the light of the three commonplaces of narrative inquiry: temporality, sociality and locality. Emerging themes are resignified considering pertinent literature to suggest implications for local university EL teacher education.